RECENT DEVELOPMENTS IN THE EXAMINATION OF THE BIOLOGY AND ANTIBIOTIC RESISTANCE MECHANISMS OF ANAEROBIC PATHOGENS - Sóki, József (Eurasian Journal of Applied Biotechnology, 2025)
Recent developments in the examination of the biology and antibiotic resistance mechanisms of anaerobic pathogens have significantly advanced our understanding of these organisms. Studies utilizing genomic and proteomic approaches have uncovered specific genetic determinants linked to virulence and resistance, revealing how pathogens like *Bacteroides fragilis* and *Clostridium difficile* adapt to antibiotic pressures. Mechanisms such as enzymatic degradation, efflux pumps, and biofilm formation have been identified as key contributors to their resilience against treatment. Additionally, the interplay between anaerobic pathogens and the human microbiome is being explored, highlighting how dysbiosis can lead to opportunistic infections. As antibiotic resistance continues to pose a major public health challenge, ongoing research is crucial for developing novel therapeutic strategies and improving diagnostic methods to effectively combat these resilient pathogens.